2019
DOI: 10.1177/1071181319631434
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian Moving Patterns during Potential Conflicts with 110 On-Road Driving Vehicles

Abstract: As the most commonly seen vulnerable road users, protection and interaction with pedestrians are key functionalities in vehicle active safety and self-driving research areas. Development and evaluation of such systems require deeper understanding of pedestrian behaviors, especially motion patterns, in different driving environments. Traditionally, most of the pedestrian movement studies rely on fixed roadside cameras in specific road locations with higher pedestrian density, like intersections and junctions. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Wang et al, 2021;W. Wu et al, 2019), demographics (Amini et al, 2019;Rasouli & Tsotsos, 2019) and type of conflict zone/crossing (Cloutier et al, 2017;Habibovic et al, 2018;R. Tian et al, 2019) have been found to affect crossing behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al, 2021;W. Wu et al, 2019), demographics (Amini et al, 2019;Rasouli & Tsotsos, 2019) and type of conflict zone/crossing (Cloutier et al, 2017;Habibovic et al, 2018;R. Tian et al, 2019) have been found to affect crossing behaviour.…”
Section: Introductionmentioning
confidence: 99%